2011
DOI: 10.4103/0975-3583.89807
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in school going children of Surat city, Western India

Abstract: Background:Early diagnosis of hypertension (HT) is an important strategy in its control. Previous studies have documented that hypertension may begin in adolescence, perhaps even in childhood. The purpose of this study was to determine the prevalence of hypertension and risk factors among school going children in Surat city, south Gujarat, India.Materials and Methods:School going children aged between 6 to 18 years, of two schools were selected by purposive sampling method and blood pressure measurements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
13
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
4
13
1
Order By: Relevance
“…In Reddy et al, study and Buch et al, study the reported prevalence of hypertension among school going adolescents was 4.4% and 6.48% respectively. 20,21 In present study 1.47% boys and 3.58% girls were hypertensive (P value 0.01), while in Reddy et al study 5.1% boys and 3.5% girls were hypertensive. 20 The present study shown 15.6% of overweight and obese adolescents had hypertension in contrast to 4.29% of nonobese adolescents (P value 0.004).…”
Section: Discussioncontrasting
confidence: 41%
“…In Reddy et al, study and Buch et al, study the reported prevalence of hypertension among school going adolescents was 4.4% and 6.48% respectively. 20,21 In present study 1.47% boys and 3.58% girls were hypertensive (P value 0.01), while in Reddy et al study 5.1% boys and 3.5% girls were hypertensive. 20 The present study shown 15.6% of overweight and obese adolescents had hypertension in contrast to 4.29% of nonobese adolescents (P value 0.004).…”
Section: Discussioncontrasting
confidence: 41%
“…)[ 37 39 38 40 41 ] Upper and upper-middle social status contributed to a higher number of obese/overweight and hypertensive children and is previously shown to be a significant risk factor. [ 25 26 29 33 34 35 36 37 39 42 ] A significant number of school children's spent 1-4 h/day viewing TV or sitting at the computer. [ 28 ] Percentage body fat was highly correlated with BMI among boys and girls over 9 years although no significant difference was observed among the age group of 7-8 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study, the prevalences of hypertension and obesity were found to be 20.09% and 8.94%, respectively (14). The exact prevalence of childhood hypertension is difficult to assess, as the results vary significantly depending on age, selection of children for the survey (general population compared with school-based survey), BP measurement methods (auscultatory compared with oscillometric), number of BP readings, number of office visits, and ethnic differences.…”
Section: Discussionmentioning
confidence: 99%